Interventions in situ à Lisbonne : étude des cas d’Os Gémeos, de Vhils, de Bicicleta sem Freio et de Nunca - Helena Elias et Inês Marques (Cahiers de Narratologie)
Recently, mural interventions have been elected as one of the outputs of street artist in various cities of the world. While the sort of composition, contours, colours, and techniques employed in the murals easily make the artist recognizable within the global infrastructure space, some of them embody, highlight or appropriate aspects of the place, concerning many degrees of site specificity. Linked to a research project that concerns public art in the frame of the luso-brazilian cultural relationship, this paper offers an interpretation of how site-specific aspects are presented in the works of Os Gémeos, Vhils, Nunca, and Bicicleta sem Freio. It also aims to discuss questions regarding the concept of site-specificity within street art murals. Although street art may be argued as having heterogeneous artist with different backgrounds raging from graffiti to fine arts that present work in galleries, favorable urban policies have open the public space to legitimize street art work outside these institutional spaces, enabling the resurgence of mural interventions as one of the trends among public art works.